The effect of root and litter on soil macroporosity of Terminalia microcarpa and Dillenia philippinensis in Purwodadi Botanical Garden - Agung Sri Darmayanti; Esti Endah Ariyanti; Luchman Hakim (The East Java Biological Society, 2015)
D. philippinensis or Sempur (Java) and T. microcarpa are dominated most of vegetation in Purwodadi Botanical Garden area that will be muddy after rain. This condition can be suspected as the effect of low soil macroporosity. This study aim was to observe the effect of root quantity and litter quality surround Terminalia and Dillenia trees. Root quantity parameters which observed were Lrv (Root Length Density) dan Drv (Dry Root Mass). Sample was taken using drilling method and roots were measured using line interception method. Soil macroporosity was measured using methylene blue staining. Litter decomposed in forest floor, it weight then measures on 12 weeks after taken. Soil macroporosity higher in soil surround Dillenia than Terminalia. Soil macroporosity surround Terminalia and Dillenia are not signifi[1]cantly correlated to Lrv (Root Length Density) dan Drv (Dry Root Mass). While, decomposition rate of litter has corre[1]lated to macroporosity, especially on Terminalia.